Investigating the Capability of Dandelion Greens to Remediate Soils Contaminated with Cadmium - Zokirov Kurbonalijon Gaybullo Ugli; Annigere S Prakash; Sarah Salah Jalal; Dahlia N. Al-Saidi; Zahraa F. Hassan (Anthropogenic Pollution)
This study aimed to explore the possibility of removing cadmium, a toxic heavy metal, from soil using Dandelion greens. To accomplish this, a greenhouse experiment was conducted with six treatments including a control, and varying concentrations of cadmium in the soil. After the plants were harvested, the concentration of cadmium was measured in the plant roots, the above-ground parts, and soil samples. The results indicated that Dandelion greens have a remarkable ability to absorb cadmium from contaminated soils. The higher the concentration of cadmium in the soil, the greater the amount of cadmium absorbed by the plant roots and the above-ground parts. Specifically, the concentration of cadmium in the above-ground parts increased by 20.4 times and in the roots by 38 times with an increase in cadmium concentration. The average amount of cadmium absorbed in the root and shoot was 69.17 and 59.14 mg/kg, respectively. Furthermore, the study found that the time required for plant purification increased with the increase of cadmium concentration, and the minimum time required for purification was found to be 5 mg/kg concentration. Dandelion greens have a relatively short growth period and high yield, making them a viable option for treating cadmium-contaminated soils. Therefore, Dandelion greens can be utilized as an ornamental plant for phytoremediation of cadmium-contaminated soils. Overall, this study highlights the potential of Dandelion greens as a cost-effective and eco-friendly solution for heavy metal pollution in soil.